Functional Characterization of Clostridium difficile Spore Coat Proteins - Permpoonpattana, Patima; Phetcharaburanin, Jutarop; Mikelsone, Anna; Dembek, Marcin; Tan, Sisareuth; Brisson, Marie-Clémence; La Ragione, Roberto; Brisson, Alain R; Fairweather, Neil; Hong, Huynh A; Cutting, Simon M (Journal of Bacteriology, 2013)
Spores of Clostridium difficile play a key role in the dissemination of this important human pathogen, and until recently little has been known of their functional characteristics. Genes encoding six spore coat proteins (cotA, cotB, cotCB, cotD, cotE, and sodA) were disrupted by ClosTron insertional mutagenesis. Mutation of one gene, cotA, presented a major structural defect in spore assembly, with a clear misassembly of the outermost layers of the spore coat. The CotA protein is most probably subject to posttranslational modification and could play a key role in stabilizing the spore coat. Surprisingly, mutation of the other spore coat genes did not affect the integrity of the spore, although for the cotD, cotE, and sodA mutants, enzyme activity was reduced or abolished. This could imply that these enzymatic proteins are located in the exosporium or alternatively that they are structurally redundant. Of the spore coat proteins predicted to carry enzymatic activity, three were confirmed to be enzymes using both in vivo and in vitro methods, the latter using recombinant expressed proteins. These were a manganese catalase, encoded by cotD, a superoxide dismutase (SOD), encoded by sodA, and a bifunctional enzyme with peroxiredoxin and chitinase activity, encoded by cotE. These enzymes being exposed on the spore surface would play a role in coat polymerization and detoxification of H2O2. Two additional proteins, CotF (a tyrosine-rich protein and potential substrate for SodA) and CotG (a putative manganese catalase) were shown to be located at the spore surface.